Alcohol-induced structural transitions in the acid-denatured Bacillus licheniformis α-amylase - Halim, A.A.A.; Zaroog, M.S.; Kadir, H.A.; Tayyab, S. (Elsevier, 2017)
Alcohol-induced structural changes in the acid-denatured Bacillus licheniformis α-amylase (BLA) at pH 2.0 were studied by far-ultra violet circular dichroism, intrinsic, three-dimensional and 8-anilino-1-naphthalene sulfonic acid (ANS) fluorescence, acrylamide quenching and thermal denaturation. All the alcohols used in this study produced partial refolding in the acid-denatured BLA as evident from the increased mean residue ellipticity at 222 nm, increased intrinsic fluorescence and decreased ANS fluorescence. The order of effectiveness of these alcohols to induce a partially folded state of BLA was found to be: 2,2,2-trifluoroethanol/tert-butanol > 1-propanol/2-propanol > 2-chloroethanol > ethanol > methanol. Three-dimensional fluorescence and acrylamide quenching results obtained in the presence of 5.5 M tert-butanol also suggested formation of a partially folded state in the acid-denatured BLA. However, 5.5 M tert-butanol-induced state of BLA showed a non-cooperative thermal transition. All these results suggested formation of a partially folded state of the acid-denatured BLA in the presence of these alcohols. Furthermore, their effectiveness was found to be guided by their chain length, position of methyl groups and presence of the substituents.